Innocent Invader. - Mather, Anne; Mills & Boon Series Special Releases (Sydney, New South Wales : HarperCollins Publishers, 2021)
Convent girl! After her sheltered life in a convent, Sarah Winter can't wait to get out into the world! She knows her job as a governess to three children is going to be a challenge - but she doesn't expect her instant, fierce attraction to the children's uncle and guardian, the dynamic Jason de Cordova. As the heat flares between them, unworldly Sarah soon finds the situation is more than she can handle! Jason is charismatic, powerful and more or less rules the small Caribbean island on which she finds herself. Most daunting of all, he is also married! But fighting her feelings soon proves impossible...especially as Jason is more than happy to cure Sarah of her innocence!
Keywords: Contemporary romance; Fiction - Romance - Contemporary; Fiction - Romance - General; Electronic books